2015
DOI: 10.1002/bit.25838
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of Bacillus licheniformis reveals a stress response mechanism in the synthesis of extracellular polymeric flocculants

Abstract: Some bioflocculants composed of extracellular polymeric substances are produced under peculiar conditions. Bacillus licheniformis CGMCC2876 is a microorganism that secretes both extracellular polysaccharides (EPS) and poly-gamma-glutamic acid (γ-PGA) under stress conditions. In this work, SWATH acquisition LC-MS/MS method was adopted for differential proteomic analysis of B. licheniformis, aiming at determining the bacterial stress mechanism. Compared with LB culture, 190 differentially expressed proteins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In the medium containing glucose at 5 g/L, the levels of SucA and SdhC decreased by 3.59- and 2.01-fold, respectively (Additional file 3 ) after the glucose was exhausted. The same results revealed that the decrease in SucA and SdhC was beneficial for both the accumulation of α-ketoglutaric acid and the increase in glutamate for producing γ-PGA [ 31 ]. Thus, glycerol metabolism was changed to glycolysis when glucose was added to the medium as a co-carbon source.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the medium containing glucose at 5 g/L, the levels of SucA and SdhC decreased by 3.59- and 2.01-fold, respectively (Additional file 3 ) after the glucose was exhausted. The same results revealed that the decrease in SucA and SdhC was beneficial for both the accumulation of α-ketoglutaric acid and the increase in glutamate for producing γ-PGA [ 31 ]. Thus, glycerol metabolism was changed to glycolysis when glucose was added to the medium as a co-carbon source.…”
Section: Resultsmentioning
confidence: 92%
“…SWATH acquisition LC–MS/MS was performed using an Eksigent nanoLC-ultra system coupled with a Triple-TOF5600 Mass Spectrometer (ABSCIEX, Canada). Details of the parameters and data analysis for SWATH were reported by Yu et al [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Production of biopolymeric compounds by bacterial strains could be unpredictable even under rigorously maintained culture conditions (Bajaj and Singhal 2011a). Stressful culture conditions may induce and improve extracellular polymeric substances production by microorganisms (Yu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2 ), which was in line with the previous studies. Since the plasmid was supposed to exhibit metabolic burden on the host and affected host gene expression and phenotype, it was suspicious that the enhancement of γ -PGA synthesis in WX-pHY300 could be an element of response or adaptation response against stress caused by pHY300 (50-53). According to this study, oxidative stress increased γ -PGA production in WX-02 by ycgN deletion or H 2 O 2 addition.…”
Section: Resultsmentioning
confidence: 99%